ChemInform Abstract: Recyclable Organocatalyst‐Promoted One‐Pot Asymmetric Synthesis of Spirooxindoles Bearing Multiple Stereogenic Centers. Issue 18 (April 2016) - Huang, Xin; Pham, Kenny; Yi, Wenbin; Zhang, Xiaofeng; Clamens, Cecilia; Hyatt, Jeremy H.; Jasinsk, Jerry P.; Tayvah, Uriel; Zhang, Wei
Abstract: A recyclable fluorous bifunctional Cinchona alkaloid/thiourea‐catalyzed, one‐pot four‐component Michael/Mannich/cyclization sequence is developed for the asymmetric synthesis of spirooxindoles containing 2‐piperidinone and tetrahydropyridine rings.